2007
DOI: 10.1562/0031-8655(2003)0780088flvapl2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Focal Length Variability and Protein Leakage as Tools for Measuring Photooxidative Damage to the Lens¶

Abstract: Hypericin is the ingredient used to standardize the popular over‐the‐counter antidepressant medication St. John's Wort. Because hypericin readily produces singlet oxygen and other excited state intermediates, it is a very efficient phototoxic agent in the eye that can potentially induce the development of the cataract photooxidative mechanism. Hypericin absorbs in the UV and visible ranges, binds to the lens crystallins (α, β and γ) and damages these proteins through a photooxidative mechanism. Effects were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The system is also used to measure ocular irritancy of contact lens solutions (39) and oxidative damage (40). Using the lens-culture system, it was found that the lens can recover in culture conditions from damage induced by different insulting factors (21,27,32,39,41).…”
Section: Discussionmentioning
confidence: 99%
“…The system is also used to measure ocular irritancy of contact lens solutions (39) and oxidative damage (40). Using the lens-culture system, it was found that the lens can recover in culture conditions from damage induced by different insulting factors (21,27,32,39,41).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, UVC radiation is completely absorbed by the ozone layer (2, 3). However UVA and some UVB radiation pass through the ozone layer, and it has been suggested that UVA and UVB irradiation mediate agerelated changes in the eye and can cause ocular disease (1, 4–10). This is of particularly importance to the cornea because it is the first layer of the eye exposed to sunlight (4–6).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have determined that hypericin inhibits the growth of retinal pigment epithelial cells ( 17 ). Our previous studies have shown that hypericin is taken up by the intact lens ( 18 ), photooxidizes lens proteins ( 19 ) and distorts the transmission of light through the lens ( 20 ). Therefore, hypericin fulfills the criterion of a potential ocular phototoxic agent.…”
Section: Introductionmentioning
confidence: 99%